Battery-grade lithium carbonate and preparation method thereof
By combining lithium carbonate in the salt lake with concentrated lithium sulfate in the waste lithium battery recycling process, and using a specific washing and mixing process, the problems of high sodium and sulfur impurities and large washing water in the recycled lithium carbonate are solved, and stable production and efficient preparation of battery-grade lithium carbonate are achieved.
Patent Information
- Application Number
- CN202411741615.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
AI Technical Summary
The recycled lithium carbonate from the recycling of the positive electrode material of waste lithium battery has high impurities content, large amount of washing water, poor stability of the finished product index of recycled lithium carbonate, and high concentration of impurities such as calcium and magnesium in salt lakes, making it difficult to refine.
The salt lake lithium carbonate is added as a raw material to the washing process in the waste lithium-ion power battery recycling process. The input ratio is calculated by calculating the index and combining the characteristics of the two, the cost of refining the salt lake lithium carbonate can be reduced, while stabilizing the regeneration of the lithium carbonate index. The specific steps include adding the lithium-containing concentrate solution to precipitate in the soluble carbonate solution, washing it with hot pure water, mixing the salt lake lithium carbonate slurry and then filtration, drying and crushing to obtain a battery-grade lithium carbonate finished product.
Through this method, the amount of washing water is reduced, the index stability of the finished lithium carbonate product is improved, the production cost is reduced, and the yield of finished products is improved.
Smart Images

Figure CN119612556A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium carbonate preparation, and in particular to battery-grade lithium carbonate and a preparation method thereof. Background Art
[0002] With the rapid development of the new energy vehicle industry, lithium ions have led to a substantial increase in the demand for lithium resources, especially lithium carbonate. As an important basic material for the production of lithium-ion battery positive electrode materials, the production and preparation process of lithium carbonate (Li2CO3) has become the focus of research and industrial attention. After the power battery is retired, lithium carbonate can be re-prepared through the recycling process. The recycling process of waste lithium-ion power batteries is mainly divided into two categories: pyrometallurgy and hydrometallurgy. Pyrometallurgy mainly relies on high temperature treatment of waste batteries, extracts metal alloys after melting, and then smelts and separates; hydrometallurgy uses acid leaching, precipitation, ion exchange and other technologies to selectively recover valuable metal ions in the battery. Compared with pyrometallurgy, hydrometallurgical process is widely used in metal extraction of waste batteries because of its less environmental pollution and lower energy consumption. In hydrometallurgy, the positive electrode material is leached by acid, and the metal ions are dissolved into the solution. For the extraction of lithium, commonly used acid leaching agents include sulfuric acid (H2SO4), hydrochloric acid (HCl), etc. By adjusting the reaction conditions, efficient leaching of lithium can be achieved. For example, when sulfuric acid is used as a leaching agent, the leaching rate of lithium can reach more than 90%. However, since a large amount of sulfate and sodium ions exist in the solution during the synthesis step and are adsorbed on the surface of lithium carbonate or coated in lithium carbonate during synthesis, the content of sodium and sulfur impurities in the regenerated lithium carbonate is a difficult problem to control.
[0003] Extracting salt lake brine is one of the important sources of lithium carbonate. China is rich in salt lake resources. However, due to the low concentration of lithium ions in salt lake brine (usually between 0.03% and 0.15%) and the high concentration of impurity ions such as calcium and magnesium, the refining process after extraction still faces many challenges. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a battery-grade lithium carbonate and a preparation method thereof, aiming to solve the technical problems that the regenerated lithium carbonate produced by recycling waste lithium battery positive electrode materials has high sodium and sulfur impurity content, large amount of washing water, poor stability of the indicators of the regenerated lithium carbonate finished product, and high concentration of impurity ions such as calcium and magnesium in salt lake lithium carbonate, making it difficult to purify.
[0005] In a first aspect, the present invention provides a method for preparing battery-grade lithium carbonate, comprising the following steps: adding the lithium-containing concentrated solution to a soluble carbonate solution to obtain a lithium carbonate precipitate, and washing the lithium carbonate precipitate with hot pure water to obtain a washing slurry; Dispersing salt lake lithium carbonate in pure water to obtain salt lake lithium carbonate slurry; The washed slurry is mixed evenly with the salt lake lithium carbonate slurry, filtered, dried and crushed to obtain the finished lithium carbonate product.
[0006] In the technical solution of the embodiment of the present application, waste lithium-ion power batteries use sulfuric acid as an acid leaching agent. When the concentrated lithium sulfate produced is used to synthesize regenerated lithium carbonate, the impurity content of sodium and sulfate is high, and multiple large-scale washing with water is required. Usually, it is necessary to wash it twice with hot pure water at a ratio of 1:20. At this time, the impurity content of sodium and sulfate can barely meet the index requirements of battery-grade lithium carbonate. However, with the fluctuation of the sodium and sulfate content in the concentrated lithium sulfate solution, the yield of lithium carbonate obtained by this process is unstable. If the amount of water is increased or another washing is added, excessive water consumption will result in a decrease in the direct yield.
[0007] Salt lake lithium carbonate has problems with high magnetic anomaly and excessive calcium and magnesium content, which requires further demagnetization and refining. However, the sodium and sulfate impurity content of the finished product of salt lake lithium carbonate is much lower than the index requirements of battery-grade lithium carbonate.
[0008] Therefore, this application adds salt lake lithium carbonate as a raw material to the washing process in the waste lithium-ion power battery recycling process, calculates the input ratio through indicators, and combines the characteristics of the two, so as to reduce the cost of refining salt lake lithium carbonate and stabilize the regeneration lithium carbonate indicators.
[0009] Preferably, the lithium-containing concentrated solution is obtained by roasting, crushing and sorting the lithium-containing waste, leaching with sulfuric acid, removing impurities and enriching the lithium-containing concentrated solution. + The concentration is 12~20g / L, Na + Concentration is 20~80g / L, SO4 2+ The concentration is 180~300g / L, Ca 2+ Concentration is 0~15mg / L, Mg 2+ The concentration is 0~10mg / L.
[0010] Preferably, the soluble carbonate is sodium carbonate, and the concentration of sodium carbonate is 70-105 g / L.
[0011] Preferably, the Na in the washing slurry and the salt lake lithium carbonate slurry are respectively + 、SO4 2+ , Ca 2+ Mg 2+ The concentration is tested, and the volume ratio of the washing slurry to the salt lake lithium carbonate slurry is determined according to the test results, so that the Na + Content ≤0.025%, SO4 2+ Content ≤0.08%, Ca 2+Content ≤0.005%, Mg 2+ Content ≤0.008% Preferably, after the soluble carbonate is heated, a lithium-containing concentrated solution is added thereto and mixed and stirred. The lithium-containing concentrated solution is added for no less than 120 minutes, and after the addition is completed, the reaction is continued for no less than 90 minutes to obtain lithium carbonate precipitate.
[0012] Preferably, the lithium carbonate precipitate is washed twice with hot pure water, and the washing steps are: the lithium carbonate precipitate is filtered and then mixed with hot pure water for washing, the mass ratio of the lithium carbonate precipitate to the hot pure water is 1:15, the washing time is not less than 60 minutes, and washing is performed twice to obtain a washed slurry.
[0013] Preferably, the mass ratio of salt lake carbonate to pure water in the salt lake lithium carbonate is 1:4.
[0014] Preferably, Na in the salt lake lithium carbonate slurry + Content is 0.01%~0.02%, SO4 2+ The content is 0.0001%~0.01%, Ca 2+ The content is 0.005%~0.001%, Mg 2+ The content is 0.005%~0.007%.
[0015] Preferably, the salt lake lithium carbonate is mixed with the washing slurry and then circulated to remove iron to obtain the salt lake lithium carbonate slurry. A permanent magnetic iron remover is used to remove magnetic foreign matter in the salt lake lithium carbonate slurry to adjust the magnetic anisotropy of the salt lake lithium carbonate slurry.
[0016] In the technical scheme of the embodiment of the present application, the lithium-containing concentrate is added to the sodium carbonate solution at a certain flow rate for reaction, which is beneficial to improve the conversion of lithium sulfate in the lithium-containing concentrate into lithium carbonate. During the synthesis, due to the high concentration of sodium sulfate in the lithium-containing concentrate, sodium and sulfate are also coated in the process of lithium carbonate crystal formation, and more sodium sulfate is attached to the surface of the lithium carbonate crystal. The synthesized lithium carbonate is washed with hot pure water at a ratio of 1:15, mainly to remove sodium and sulfate attached to the surface. The salt lake lithium carbonate is cyclically deironed and tested. According to the test results, it is mixed with the second washed lithium carbonate to make the salt lake lithium carbonate with low sodium and sulfur and the second washed lithium carbonate with low calcium and magnesium mixed to stabilize the indicators and reach the level of battery-grade lithium carbonate.
[0017] In the second aspect, the present application embodiment provides a battery-grade lithium carbonate, wherein Na + Content is 0.016%~0.018%, SO4 2- The content is 0.044%~0.05%, Ca 2+ The content is 0.0005%~0.0008%, Mg 2+ The content is 0.0008%~0.001%.
[0018] Different from the existing technical solutions, the beneficial effects of this application include: 1. This application adds salt lake lithium carbonate as a raw material to the washing process in the waste lithium-ion power battery recycling process. By calculating the input ratio through indicators, and combining the characteristics of salt lake lithium carbonate and concentrated lithium sulfate obtained in the recycling process, it can achieve the effect of reducing the cost of refining salt lake lithium carbonate and stabilizing the regenerated lithium carbonate indicators.
[0019] 2. By adopting the technical solution of the present application, the amount of water used for primary and secondary washing is reduced from 1:20 (mass ratio of washing slurry and hot pure water) to 1:15, and the finished product index sulfate 750-950ppm is reduced to sulfate 400-600ppm, while the yield is increased to 100%. It not only reduces the amount of water used for washing, but also greatly enhances the stability and controllability of the finished battery-grade lithium carbonate indicators, reduces production costs and improves the finished product yield.
[0020] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 This is a process roadmap for an embodiment of the present application. DETAILED DESCRIPTION
[0023] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0025] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0026] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0027] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0028] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0029] When sulfuric acid is used as a leaching agent, the leaching rate of lithium in the cathode material of waste lithium-ion batteries can reach more than 90%. However, since a large amount of sulfate and sodium ions exist in the solution during the synthesis step and are adsorbed on the surface of lithium carbonate or coated in lithium carbonate during synthesis, the content of sodium and sulfur impurities in the regenerated lithium carbonate is a difficult indicator to control.
[0030] Extracting salt lake brine is one of the important sources of lithium carbonate. China is rich in salt lake resources. However, due to the low concentration of lithium ions in salt lake brine (usually between 0.03% and 0.15%) and the high concentration of impurity ions such as calcium and magnesium, the refining process after extraction still faces many challenges.
[0031] In order to solve the technical problems that the regenerated lithium carbonate produced by recycling waste lithium battery positive electrode materials has high sodium and sulfur impurity content, large washing water consumption, poor stability of the indicators of the regenerated lithium carbonate finished product, and high concentration of impurity ions such as calcium and magnesium in salt lake lithium carbonate, which makes it difficult to purify, the present application provides a battery-grade lithium carbonate and a preparation method thereof, wherein salt lake lithium carbonate is added as a raw material to the washing process in the waste lithium-ion power battery recycling process, the input ratio is calculated through indicators, and the characteristics of the salt lake lithium carbonate and the concentrated lithium sulfate obtained in the recycling process are combined, so as to achieve the effect of reducing the cost of refining salt lake lithium carbonate and stabilizing the indicators of regenerated lithium carbonate.
[0032] In a first aspect, the present invention provides a method for preparing battery-grade lithium carbonate, comprising the following steps: adding the lithium-containing concentrated solution to a soluble carbonate solution to obtain a lithium carbonate precipitate, and washing the lithium carbonate precipitate with hot pure water to obtain a washing slurry; Dispersing salt lake lithium carbonate in pure water to obtain salt lake lithium carbonate slurry; The washed slurry is mixed evenly with the salt lake lithium carbonate slurry, filtered, dried and crushed to obtain the finished lithium carbonate product.
[0033] In the technical solution of the embodiment of the present application, waste lithium-ion power batteries use sulfuric acid as an acid leaching agent. When the concentrated lithium sulfate produced is used to synthesize regenerated lithium carbonate, the impurity content of sodium and sulfate is high, and multiple large-scale washing with water is required. Usually, it is necessary to wash it twice with hot pure water at a ratio of 1:20. At this time, the impurity content of sodium and sulfate can barely meet the index requirements of battery-grade lithium carbonate. However, with the fluctuation of the sodium and sulfate content in the concentrated lithium sulfate solution, the yield of lithium carbonate obtained by this process is unstable. If the amount of water is increased or another washing is added, excessive water consumption will result in a decrease in the direct yield.
[0034] Salt lake lithium carbonate has problems with high magnetic anomaly and excessive calcium and magnesium content, which requires further demagnetization and refining. However, the sodium and sulfate impurity content of the finished product of salt lake lithium carbonate is much lower than the index requirements of battery-grade lithium carbonate.
[0035] Therefore, this application adds salt lake lithium carbonate as a raw material to the washing process in the waste lithium-ion power battery recycling process, calculates the input ratio through indicators, and combines the characteristics of the two, so as to reduce the cost of refining salt lake lithium carbonate and stabilize the regeneration lithium carbonate indicators.
[0036] Preferably, the lithium-containing concentrated solution is obtained by roasting, crushing and sorting the lithium-containing waste, leaching with sulfuric acid, removing impurities and enriching the lithium-containing concentrated solution. + The concentration is 12~20g / L, Na + Concentration is 20~80g / L, SO4 2+The concentration is 180~300g / L, Ca 2+ Concentration is 0~15mg / L, Mg 2+ The concentration is 0~10mg / L.
[0037] Preferably, the soluble carbonate is sodium carbonate, and the concentration of sodium carbonate is 70-105 g / L.
[0038] Preferably, the Na in the washing slurry and the salt lake lithium carbonate slurry are respectively + 、SO4 2+ , Ca 2+ Mg 2+ The concentration is tested, and the volume ratio of the washing slurry to the salt lake lithium carbonate slurry is determined according to the test results, so that the Na + Content ≤0.025%, SO4 2+ Content ≤0.08%, Ca 2+ Content ≤0.005%, Mg 2+ Content ≤0.008%.
[0039] Preferably, after the soluble carbonate is heated, a lithium-containing concentrated solution is added thereto and mixed and stirred. The lithium-containing concentrated solution is added for no less than 120 minutes, and after the addition is completed, the reaction is continued for no less than 90 minutes to obtain lithium carbonate precipitate.
[0040] Preferably, the lithium carbonate precipitate is washed twice with hot pure water, and the washing steps are: the lithium carbonate precipitate is filtered and then mixed with hot pure water for washing, the mass ratio of the lithium carbonate precipitate to the hot pure water is 1:15, the washing time is not less than 60 minutes, and washing is performed twice to obtain a washed slurry.
[0041] Preferably, the mass ratio of salt lake carbonate to pure water in the salt lake lithium carbonate slurry is 1:4.
[0042] Preferably, Na in salt lake lithium carbonate + Content is 0.01%~0.02%, SO4 2+ The content is 0.0001%~0.01%, Ca 2+ The content is 0.005%~0.001%, Mg 2+ The content is 0.005%~0.007%.
[0043] Preferably, the salt lake lithium carbonate is mixed with the washing slurry and then circulated to remove iron to obtain the salt lake lithium carbonate slurry. A permanent magnetic iron remover is used to remove magnetic foreign matter in the salt lake lithium carbonate slurry to adjust the magnetic anisotropy of the salt lake lithium carbonate slurry.
[0044] In the technical scheme of the embodiment of the present application, the lithium-containing concentrate is added to the sodium carbonate solution at a certain flow rate for reaction, which is beneficial to improve the conversion of lithium sulfate in the lithium-containing concentrate into lithium carbonate. During the synthesis, due to the high concentration of sodium sulfate in the lithium-containing concentrate, sodium and sulfate are also coated in the process of lithium carbonate crystal formation, and more sodium sulfate is attached to the surface of the lithium carbonate crystal. The synthesized lithium carbonate is washed with hot pure water at a ratio of 1:15, mainly to remove sodium and sulfate attached to the surface. The salt lake lithium carbonate is cyclically deironed and tested. According to the test results, it is mixed with the second washed lithium carbonate to make the salt lake lithium carbonate with low sodium and sulfur and the second washed lithium carbonate with low calcium and magnesium mixed to stabilize the indicators and reach the level of battery-grade lithium carbonate.
[0045] In the second aspect, the present application embodiment provides a battery-grade lithium carbonate, wherein Na + Content is 0.016%~0.018%, SO4 2- The content is 0.044%~0.05%, Ca 2+ The content is 0.0005%~0.0008%, Mg 2+ The content is 0.0008%~0.001%.
[0046] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the finished product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional finished products that can be obtained commercially.
[0047] 1. Preparation method Example 1 Into the reactor into 9.2m 3 The sodium carbonate solution was then heated to 80 degrees, and 13m of concentrated lithium sulfate solution was introduced during the heating process. 3 The addition was completed within 120 minutes, the stirring speed was 200 rpm, and after reacting for 90 minutes, the mixture was filtered and washed once.
[0048] The lithium content in the concentrated lithium sulfate solution is 16g / L, sodium 76g / L, sulfate 294g / L, calcium 15g / L, and magnesium 7mg / L; the sodium carbonate solution is 85g / L.
[0049] The first washing conditions were as follows: hot pure water was introduced at a mass ratio of 1:15, the temperature was maintained at 85°C, the rotation speed was 200 rpm, and the washing was continued for 60 min. After the filtration, the second washing was performed.
[0050] Secondary washing conditions: hot pure water is introduced at a mass ratio of 1:15, the temperature is maintained at 85°C, the rotation speed is 200 rpm, and the process is continued for 60 min to obtain a secondary washing slurry, which enters the batch tank after washing is completed.
[0051] Salt lake lithium carbonate and pure water are mixed in a volume ratio of 1:4 and then circulated to remove iron to obtain salt lake lithium carbonate slurry. The Qinghai Lake lithium carbonate selected in this embodiment has Na + The content is 0.0174%, SO4 2+ The content is 0.0001%, Ca 2+ The content is 0.001%, Mg 2+ The content is 0.0071%.
[0052] The Na in the washing slurry and the salt lake lithium carbonate slurry were + 、SO4 2+ , Ca 2+ Mg 2+ The concentration is tested, and the volumes of the washing slurry and the salt lake lithium carbonate slurry are determined according to the test results. After mixing them in a batch tank in a volume ratio of secondary washing slurry: salt lake lithium carbonate slurry = 18:6, they are passed into a filter press, dried, crushed, and packaged to obtain a finished lithium carbonate product.
[0053] Example 2 Into the reactor into 9.2m 3 The sodium carbonate solution was then heated to 80 degrees, and 13m of concentrated lithium sulfate solution was introduced during the heating process. 3 The addition was completed within 120 minutes, the stirring speed was 200 rpm, and after reacting for 90 minutes, the mixture was filtered and washed once.
[0054] The lithium content in the concentrated lithium sulfate solution is 16g / L, sodium 76g / L, sulfate 294g / L, calcium 15g / L, and magnesium 7mg / L; the sodium carbonate solution is 85g / L.
[0055] The first washing conditions were as follows: hot pure water was introduced at a mass ratio of 1:15, the temperature was maintained at 85°C, the rotation speed was 200 rpm, and the washing was continued for 60 min. After the filtration, the second washing was performed.
[0056] Secondary washing conditions: hot pure water is introduced at a mass ratio of 1:15, the temperature is maintained at 85°C, the rotation speed is 200 rpm, and the process is continued for 60 min to obtain a secondary washing slurry, which enters the batch tank after washing is completed.
[0057] Salt lake lithium carbonate and pure water are mixed in a volume ratio of 1:4 and then circulated to remove iron to obtain salt lake lithium carbonate slurry. The Qinghai Lake lithium carbonate selected in this embodiment has Na + The content is 0.0119%, SO4 2+The content is 0.0001%, Ca 2+ The content is 0.0012%, Mg 2+ The content is 0.0057%.
[0058] The Na in the washing slurry and the salt lake lithium carbonate slurry were + 、SO4 2+ , Ca 2+ Mg 2+ The concentration is tested, and the volumes of the washing slurry and the salt lake lithium carbonate slurry are determined according to the test results. After mixing them in a batch tank in a volume ratio of secondary washing slurry: salt lake lithium carbonate slurry = 18:6, they are passed into a filter press, dried, crushed, and packaged to obtain a finished lithium carbonate product.
[0059] Example 3 Into the reactor into 9.2m 3 The sodium carbonate solution was then heated to 80 degrees, and 13m of concentrated lithium sulfate solution was introduced during the heating process. 3 The addition was completed within 120 minutes, the stirring speed was 200 rpm, and after reacting for 90 minutes, the mixture was filtered and washed once.
[0060] The lithium content in the concentrated lithium sulfate solution is 16g / L, sodium 76g / L, sulfate 294g / L, calcium 15g / L, and magnesium 7mg / L; the sodium carbonate solution is 85g / L.
[0061] The first washing conditions were as follows: hot pure water was introduced at a mass ratio of 1:15, the temperature was maintained at 85°C, the rotation speed was 200 rpm, and the washing was continued for 60 min. After the filtration, the second washing was performed.
[0062] Secondary washing conditions: hot pure water is introduced at a mass ratio of 1:15, the temperature is maintained at 85°C, the rotation speed is 200 rpm, and the process is continued for 60 min to obtain a secondary washing slurry, which enters the batch tank after washing is completed.
[0063] Salt lake lithium carbonate and pure water are mixed in a volume ratio of 1:4 and then circulated to remove iron to obtain salt lake lithium carbonate slurry. The Qinghai Lake lithium carbonate selected in this embodiment has Na + The content is 0.0107%, SO4 2+ The content is 0.0001%, Ca 2+ The content is 0.0014%, Mg 2+ The content is 0.0054%.
[0064] The Na in the washing slurry and the salt lake lithium carbonate slurry were + 、SO4 2+ , Ca 2+ Mg 2+The concentration is tested, and the volumes of the washing slurry and the salt lake lithium carbonate slurry are determined according to the test results. After mixing them in a batch tank in a volume ratio of secondary washing slurry: salt lake lithium carbonate slurry = 18:6, they are passed into a filter press, dried, crushed, and packaged to obtain a finished lithium carbonate product.
[0065] Comparative Example 1 Into the reactor into 9.2m 3 The sodium carbonate solution was then heated to 80°C, and concentrated lithium sulfate solution was introduced during the heating process. The addition was completed within 120 minutes, the stirring speed was 200 rpm, and after reacting for 90 minutes, the solution was filtered and washed once.
[0066] The lithium content in the concentrated lithium sulfate solution is 16g / L, sodium 76g / L, sulfate 294g / L, calcium 15g / L, and magnesium 7mg / L; the sodium carbonate solution is 85g / L.
[0067] The first washing conditions were as follows: hot pure water was introduced at a mass ratio of 1:20, the temperature was maintained at 85°C, the rotation speed was 200 rpm, and the washing was continued for 60 minutes. After the filtration, the second washing was performed.
[0068] Secondary washing conditions: Pass hot pure water at a mass ratio of 1:20, maintain the temperature at 85°C, rotate at 200 rpm, and continue for 60 minutes. After washing, enter the batch tank.
[0069] The batch tank only serves as a transfer point, and then it is passed into the filter press, dried, crushed and packaged to obtain the finished product.
[0070] 2. Test Method Na + 、SO4 2+ , Ca 2+ Mg 2+ Concentration detection method: Inductively coupled plasma optical emission spectrometer (ICP-OES) was used for detection.
[0071] III. Analysis of test results of various embodiments and comparative examples The Na in the washed slurry residue obtained after filter pressing of the washed slurry obtained in Example 1 and Comparative Example 1 and the lithium carbonate product were + 、SO4 2+ , Ca 2+ Mg 2+ The concentration was tested. Three batches of tests were carried out on Example 1, in which the washing slurry residue and the finished lithium carbonate products were marked as serial numbers 1 to 3 respectively. The test results are shown in Table 1 below.
[0072] Table 1 Ion concentration test results at each stage in Example 1 and Comparative Example 1
[0073] As can be seen from Table 1, by using the method in the embodiment of the present application to prepare battery-grade lithium carbonate products, the amount of water used for secondary washing is reduced by 25% compared with the process in the comparative example. At the same time, the process of jointly preparing battery-grade lithium carbonate products using regenerated lithium carbonate and salt lake lithium carbonate has obvious advantages in impurity index control and yield stability.
[0074] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing battery-grade lithium carbonate, characterized in that: The steps include: adding the lithium-containing concentrated solution to a soluble carbonate solution to obtain a lithium carbonate precipitate, and washing the lithium carbonate precipitate with hot pure water to obtain a washing slurry; Dispersing salt lake lithium carbonate in pure water to obtain salt lake lithium carbonate slurry; The washed slurry is mixed evenly with the salt lake lithium carbonate slurry, filtered, dried and crushed to obtain the finished lithium carbonate product.
2. The method for preparing battery-grade lithium carbonate according to claim 1, wherein The lithium-containing concentrated solution is obtained by roasting, crushing and sorting, leaching with sulfuric acid, removing impurities and enriching the lithium-containing waste. + The concentration is 12~20g / L, Na + Concentration is 20~80g / L, SO4 2+ The concentration is 180~300g / L, Ca 2+ Concentration is 0~15mg / L, Mg 2+ The concentration is 0~10mg / L.
3. The method for preparing battery-grade lithium carbonate according to claim 1, characterized in that: The soluble carbonate is sodium carbonate, and the concentration of sodium carbonate is 70-105 g / L.
4. The method for preparing battery-grade lithium carbonate according to claim 1, wherein The Na in the washing slurry and the salt lake lithium carbonate slurry were + 、SO4 2+ , Ca 2+ Mg 2+ The concentration is tested, and the volume ratio of the washing slurry to the salt lake lithium carbonate slurry is determined according to the test results, so that the Na + Content ≤0.025%, SO4 2+ Content ≤0.08%, Ca 2+ Content ≤0.005%, Mg 2+ Content ≤0.008%.
5. The method for preparing battery-grade lithium carbonate according to claim 1, characterized in that: After the soluble carbonate is heated, a lithium-containing concentrated solution is added thereto and mixed and stirred. The lithium-containing concentrated solution is added for no less than 120 minutes. After the addition is completed, the reaction is continued for no less than 90 minutes to obtain lithium carbonate precipitation.
6. The method for preparing battery-grade lithium carbonate according to claim 1, characterized in that: The lithium carbonate precipitate is washed twice with hot pure water, and the washing steps are: the lithium carbonate precipitate is filtered and mixed with hot pure water for washing, the mass ratio of the lithium carbonate precipitate to the hot pure water is 1:15, the washing time is not less than 60 minutes, and washing is performed twice to obtain a washed slurry.
7. The method for preparing battery-grade lithium carbonate according to claim 1, characterized in that: The mass ratio of salt lake lithium carbonate to pure water in the salt lake lithium carbonate slurry is 1:
4.
8. The method for preparing battery-grade lithium carbonate according to claim 7, characterized in that: The Na in the salt lake lithium carbonate + Content is 0.01%~0.02%, SO4 2+ The content is 0.0001%~0.01%, Ca 2+ The content is 0.005%~0.001%, Mg 2+ The content is 0.005%~0.007%.
9. The method for preparing battery-grade lithium carbonate according to claim 1, characterized in that: The salt lake lithium carbonate is mixed with the washing slurry and then circulated to remove iron to obtain salt lake lithium carbonate slurry.
10. A battery-grade lithium carbonate, characterized in that: The method for preparing lithium carbonate according to any one of claims 1 to 9 is used to prepare the lithium carbonate, wherein Na + Content is 0.016%~0.018%, SO4 2- The content is 0.044%~0.05%, Ca 2+ The content is 0.0005%~0.0008%, Mg 2+ The content is 0.0008%~0.001%.